Метаболічний синдром і його корекція - Звягинцева, Т. Д.; Плутенко, І. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
Article deals with the problem of metabolic syndrome. Treatment of metabolic syndrome was made with Siofor and Berlition. Decrease of glicemia, total cholesterol, triglycerids and low density lipoproteins in blood serum, increase of high density lipoproteins were proved. Quality of life in patients was improved.